“Ninja Technique” for Percutaneous Completion of Partial-Thickness, Articular-Sided Rotator Cuff Tears - Sacksteder, Nicholas J. (Arthrosc Tech, 2021)
Rotator cuff tears are a common source of shoulder pain and dysfunction. Owing to the multifaceted nature of these injuries, various viable methodologies exist for their surgical and nonsurgical management. Among surgically managed patients, those with PASTA (partial articular supraspinatus tendon avulsion) lesions require careful consideration of technique. Both transtendinous repair and tear completion with subsequent repair have been described. Both techniques offer unique benefits. In this publication, we offer an expedient and minimally invasive technique for tear completion and subsequent repair. The “ninja technique” uses localization via a spinal needle and tear completion with an arthroscopically manipulated scalpel blade. Conversion of partial tears to full-thickness tears using the ninja technique allows for technically simplified repairs while maximizing available tendon length.